POTENTIAL DEVELOPMENT OF THE SERPONG LAGOON TANGERANG AREA BASED ON VISUAL AESTHETICS - Anisa Rumondang Ristanti; Qurrotu ‘Aini Besila; Setiawan, Eko Adhy (Universitas Trisakti, 2024)
Serpong Lagoon is located in Tangerang, Banten, which is a real estate area with affordable prices for middle- and upper-middle-class families, covering an area of 30 square hectares. Serpong Lagoon has quite diverse facilities and infrastructure. This area has three existing lakes located in open-space areas and in settlements, but there is a lack of utilization of the visual aesthetic potential and good aesthetic quality of the site. The purpose of this research is to find out the potential of visual aesthetics on the site by using the design principles that form the visual landscape and to find out the aesthetic aspects as the basis for developing landscape design, both spatial arrangement activities and visual aesthetics in the area. This research uses the method, namely SBE (Scenic Beauty Estimation). The result of this research is an increase in the visual aesthetic value of the landscape, based on the research assessment.